Cutting edge MLOps from zero with Hugging Face and OpenAI. (Pragmatic AI Solutions, 2022)
Cutting Edge MLOps from Zero with Hugging Face and OpenAI Learn by doing This video course takes you from zero all the way to building solutions using MLOps. First the theory of MLOps is explained, then you will learn how to build a MLOps style solution from scratch using Hugging Face and OpenAI. You will also learn to use AI tools like Github Copilot, Hugging Face Spaces, and OpenAI Codex. Learning Objectives Learn to use Github Codespaces and customize your environment with devcontainer.json Learn the foundations of MLOps Explore new topics in the upcoming book Enterprise MLOps by O'Reilly Learn to use Github Actions to test AI projects Learn to use Github Copilot to write code for both Hugging Face and OpenAI Learn to build AI solutions using GPT-3 Additional Popular Resources Pytest Master Class AWS Solutions Architect Professional Course Github Actions and GitOps in One Hour Video Course Jenkins CI/CD and Github in One Hour Video Course AWS Certified Cloud Practitioner Video Course Advanced Testing with Pytest Video Course AWS Solutions Architect Certification In ONE HOUR Python for DevOps Master Class 2022: CI/CD, Github Actions, Containers, and Microservices MLOPs Foundations: Chapter 2 Walkthrough of Practical MLOps Learn Docker containers in One Hour Video Course Introduction to MLOps Walkthrough AZ-900 (Azure Fundamentals) Quick reference guide 52 Weeks of AWS Episode 8: Infrastructure as Code with CDK and AWS Lambda Learn GCP Cloud Functions in One Hour Video Course Python Devops in TWO HOURS! MLOps Platforms From Zero: DatMLOps Platforms From Zero: Databricks, MLFlow/MLRun/SKLearn AWS Machine Learning Certification In ONE HOUR Fast, documented Machine Learning APIs with FastAPI Zero to One: AWS Lambda with SAM and Python in One Hour AWS Storage Solutions 2022: EBS/S3/EFS/Glacier Python Bootcamp for Data Testing In Python book Minimal Python book Practical MLOps book Python for DevOps-Playlist.